PENGARUH ISLAM TERHADAP TEKS MELAYU DAN UNDANG-UNDANG MELAYU - Yusoff, Mohd Alwee (Jurnal Syariah, 2019)
The writer elaborates how the Arabic language and Islam have their influence on the Malay language in the aspects of vocabulary, alphabetical and grammatical; on the various genre in the Classical Malay Literature as well as the legal texts.